Changes in mortality due to major alcohol‐related diseases in four Nordic countries, France and Germany between 1980 and 2009: a comparative age–period–cohort analysis. (14th July 2015) - Kraus, Ludwig; Østhus, Ståle; Amundsen, Ellen J.; Piontek, Daniela; Härkönen, Janne; Legleye, Stéphane; Bloomfield, Kim; Mäkelä, Pia; Landberg, Jonas; Törrönen, Jukka
Abstract Aims To investigate age, period and cohort effects on time trends of alcohol‐related mortality in countries with different drinking habits and alcohol policies. Design and setting Age–period–cohort (APC) analyses on alcohol‐related mortality were conducted in Denmark, Finland, Norway, Sweden, France and Germany. Participants Cases included alcohol‐related deaths in the age range 20–84 years between 1980 and 2009. Measurements Mortality data were taken from national causes of death registries and covered the ICD codes alcoholic psychosis, alcohol use disorders, alcoholic liver disease and toxic effect of alcohol. Findings In all countries changes across age, period and cohort were found to be significant for both genders [effect value with confidence interval (CI) shown in Supporting information, Table S1]. Period effects pointed to an increase in alcohol‐related mortality in Denmark, Finland and Germany and a slightly decreasing trend in Sweden, while in Norway an inverse U‐shaped curve and in France a U‐shaped curve was found. Compared with the cohorts born before 1960, the risk of alcohol‐related mortality declined substantially in cohorts born in the 1960s and later. Pairwise between‐country comparisons revealed more statistically significant differences for period (P < 0.001 for all 15 comparisons by gender) than for age [P < 0.001 in seven (men) and four (women) of 15 comparisons] or cohort [P < 0.01 in two (men) and three (women) of 15 comparisons]. Conclusions Strong period effects suggest that temporal changes in alcohol‐related mortality in Denmark, Finland, Norway, Sweden, France and Germany between 1980 and 2009 were related to secular differences affecting the whole population and that these effects differed across countries.